PERANAN HEART RATE TERHADAP KUALITAS CITRA PENGGUNAAN â€œCOVID-19â€ WINDOW UNTUK PEMERIKSAAN CT-SCAN THORAX POLOS PADA PASIEN SUSPEK COVID-19 - Mayasari, Anisa (Perhimpunan Radiografer Indonesia (PARI), 2020)
Background: Non-contrast chest CT-Scan is one of the COVID-19 screening methods. At Panti Waluyo hospital of Surakarta, Non-contrast chest CT-Scan did not use the HRCT technique, low-dose technique, Lung Window, and Mediastinum Window, but used a standard-dose technique and â€œCOVID-19â€ window. Methods: The research was conducted at Panti Waluyo hospital of Surakarta, scanning process using GE Brightspeed 8 Slices CT-Scan. The position of the patient is supine feet first, the midline is at the midsagittal plane and axillary line, the scanning process begins with a vertical and horizontal scout photo, scanning area from Thoracal 1st to lumbar 3rd, using a helical scan, and â€œCOVID-19â€ window with 120 kV, 100 mA, 0.8 s, 5 mm slice thickness, FoV 34 cm, gantry tilt 0 Â°, reconstruction 1.25 mm, pitch 1.35: 1, window width 1600, and window level -250. Results: The expertise of Radiologists indicates bilateral pneumonia (typical COVID-19). The